Luxury and Rubble Civility and Dispossession in the New Saigon - Harms, Erik (University of California Press, 2016)
Luxury and Rubble is the tale of two cities in Ho Chi Minh City. It is the story of two planned, mixed-use residential and commercial developments that are changing the face of Vietnam's largest city. Since the early 1990s, such developments have been steadily reorganizing urban landscapes across the country. For many Vietnamese, they are a symbol of the country's emergence into global modernity and of post-socialist economic reforms. However, they are also sites of great contestation, sparking land disputes and controversies over how to compensate evicted residents. In this penetrating ethnography, Erik Harms vividly portrays the human costs of urban reorganization as he explores the complex and sometimes contradictory experiences of individuals grappling with the forces of privatization in a socialist country. "With captivating ethnography and trenchant analysis, Erik Harms delves deeply into two communities created and destroyed by redevelopment in contemporary Ho Chi Minh City. He poignantly shows how master plans defining personhood in terms of property rights empower some to live in luxury, while leaving others in the rubble of dispossession." -ANN MARIE LESHKOWICH, author of Essential Trade: Vietnamese Women in a Changing Marketplace "Beautifully written... A remarkable achievement in urban studies and a must-read for anyone interested in changing spatial form, sociality, rights consciousness, and class dynamics in neoliberal times." -LI ZHANG, author of In Search of Paradise: Middle-Class Living in a Chinese Metropolis "Once in a while, a book comes along and makes us rethink how cities and capitalism work. Luxury and Rubble is one of those, giving us new conceptual insights into urbanism and doing so through an intensely lived and beautifully narrated ethnography." -ANANYA ROY, editor of Worlding Cities: Asian Experiments and the Art of Being Global ERIK HARMS is Associate Professor of Anthropology and Southeast Asia Studies at Yale University and the author of Saigon's Edge: On the Margins of Ho Chi Minh City.